Effect of Cr/Al contents on the 475ºC age-hardening in oxide dispersion strengthened ferritic steels. (December 2016) - Han, Wentuo; Yabuuchi, Kiyohiro; Kimura, Akihiko; Ukai, Shigeharu; Oono, Naoko; Kaito, Takeji; Torimaru, Tadahiko; Hayashi, Shigenari
Highlights: The 12Cr and 18Cr-ODSs have different age-hardening tendencies by increasing Al. 9 wt.% Al suppresses the age-hardening and formation of α′ phase in 18Cr-ODS steel. ODS steels possess a lower age-hardening susceptibility than non-ODS steels. Abstract: The age-hardening in oxide dispersion strengthened (ODS) ferritic steels with various additions of Cr (12, 15 and 18 wt.%) and Al (0, 5, 7 and 9 wt.%) were investigated. After 5000 h aging at 475 º C, the hardness increases in all these ODS steels, while the increased level depends on the Cr/Al contents. In 12Cr-ODS steels, the more the Al, the higher the increased hardness is. However, in 18Cr-ODS steels, higher Al addition suppresses the age-hardening. TEM observations of 18Cr-ODS steels reveal that 9Al suppresses the formation of Cr-enriched α' phase, while the 18Cr-5Al-ODS steel comprises a plenty of α′ phases. Adding Zr in ODS steels appears to increase the age-hardening. The susceptibility to age-hardening is remarkably lower in the ODS ferritic steels than in the non-ODS ferritic steel with the similar concentration of Cr.